STRATEGI RETENSI PELANGGAN MELALUI CUSTOMER-TIER PROGRAMS - Nanda Eka Fitriani; Tetty Herawaty; Lina Auliana; Cecep Safa’atul Barkah (Universitas Lancang Kuning, 2022)
This study aims to describe the purchase habits of Nunu Leather resellers and formulated strategies for the retention while increasing the profitability of resellers in order to make repeated purchases in larger and more stable quantities. In formulating the strategy, various analyses such as internal-based resources, VRIN framework, identification of Sustainable Competitive Advantage (SCA), and TOWS analysis are carried out. From the various analyses, a customer-tier strategy is formulated in the form of membership that is expected to solve the problems of Nunu Leather.